A century of human-induced environmental changes and the combined roles of nutrients and land use in Lake Victoria catchment on eutrophication - Njagi, Dennis M.; Joyanto, Routh; Odhiambo, Moses; Luo, Chen; Laxmi, Gayatri Basapuram; Olago, Daniel; Val, Klump; Curt, Stager (Science of the Total Environment, 2022)
Lake Victoria, a lifeline for millions of people in East Africa, is affected by anthropogenic activities resulting in eutrophication and impacting the aquatic life and water quality. Therefore, understanding the ongoing changes in the catchment is critical for its restoration. In this context, catchment and lake sediments are important archives in tracing nutrient inputs and their dominant sources to establish causality with human activities and productivity shifts. In this study, we determine the 1) changes in concentrations of total organic carbon (TOC), black carbon (BC), total nitrogen (TN), C/N ratio, and phosphorous (P) fractions in catchment sediments and the open lake, 2) distribution of diatom population in the lake, and 3) land use and land cover changes in the catchment. The distribution of TOC, BC, TN, C/N, and P correlate while showing spatial and temporal variations. In particular, the steady increase in BC confirms atmospheric inputs from anthropogenic activities in the catchment. However, lake sediments show more variations than catchment-derived sediments in geochemical trends. Notably, the catchment has undergone dramatic land use changes since the 1960s (post-independence). This change is most evident in satellite records from 1985 to 2014, which indicate accelerated human activities. For example, urban growth (666–1022%) and agricultural expansion (23–48%) increased sharply at the expense of a decline in forest cover, grassland, and woodlands in the catchment. Cities like Kisumu and Homa Bay expanded, coinciding with rapid population growth and urbanization. Consequently, nutrient inputs have increased since the 1960s, and this change corresponds with the divergence of diatom communities in the lake. In addition, the transition to Nitzschia and cyanobacteria mark increasing cultural eutrophication in the lake. The geochemical trends and statistical data support our inference(s) and provide insights into urban development and agriculture practices, which propelled increased nutrients from the catchment and productivity shifts in the lake.